The community standard: toward a model of community journalism decision making - Lessman, Justin R (Kansas State University, 2007)
This study describes and maps the process journalists employ when deciding issues of coverage, content, and treatment of news at community newspapers within the context of community standards. Much scholarship has been devoted to how journalists should make ethical decisions of news judgment in accordance with moral, ethical, and social responsibility theory. But little has been done in the way of describing and mapping how journalists – specifically, community journalists – actually make these on-deadline news decisions and how the concept of community standards plays into those decisions. Through the use of naturalistic inquiry methodology, in this case, a triangulation of qualitative depth interview methods – informant and ethnographic – within the context of society, this research describes the factors considered by community journalists when faced with decisions of news judgment, how that process takes place, and how and where community standards fit into that process. Data indicate that values and value-based moral and ethical reasoning are tempered by at least three considerations in the decision-making process: (1) how coverage and treatment will affect the journalist, (2) how coverage and treatment will affect others, and (3) the public instructional value, before being filtered through a screen of community standards prior to the final rendering of a news judgment decision. Furthermore, findings offer a base on which to construct a model of community journalism decision making, useful for study and discussions of ethical decision making among community journalism scholars, instructors, and students, and for its applications in practical situations by future or novice community journalists.
Keywords: Community journalism; Media ethics; Decision making; Social influence; Journalism (0391); Mass Communications (0708)